PENGEMBANGAN E-MODUL IPA BERBANTUAN FLIP PDF PROFESSIONAL PADA KONSEP PENCEMARAN AIR - Azizah, Imarhotul; Tamam, Badrud; Wahyuni, Eva Ari; Wulandari, Ana Yuniasti Retno; Yasir, Mochammad (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2023)
The development research aims to determine the feasibility of the media, student responses, and produce a product in the form of a science e-module assisted by Flip PDF Professional on the concept of water pollution. We used the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The data collection technique used a questionnaire. The results showed that the science e-module media assisted by Flip PDF Professional on the water pollution concept developed was suitable for students to use. The feasibility of the IPA e-module media can be seen from the results of the media expert's feasibility test of 0.84 with a very valid category, the material expert's feasibility test of 0.81 with a very valid category, readability questionnaire of 82.25% with a very good category on large-scale trial subjects, and the results of student response questionnaires 84.63% with a very good category on large-scale trial subjects. We concluded that the science e-module media assisted by Flip PDF Professional on the concept of water pollution is suitable for use for seventh grade junior high school students.